PERSEPSI MASYARAKAT KELURAHAN PINOKALAN DALAM PELAKSANAAN PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KELURAHAN PINOKALAN KOTA BITUNG SULAWESI UTARA - Audrey Runtukahu; Ferdinand Kerebungu; Yoseph Santie (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2021)
The problem in this study is about the perception of pinokalan village community regarding the assistance of Kota Tanpa Kumuh Program (KOTAKU) where they are concerned about the inability of the opportunity to receive this assistance and the purpose of this research is to know and describe the perception of pinokalan village community in the implementation of KOTAKU program. In this study using qualitative research method with observation and interview data collection techniques. And the results of this study show that the perception of the people of Pinokalan Village that we do not receive assistance kotaku program from the government when our environment is organized and not worth our stay because of the densely populated conditions and only a few residents of our village who get assistance in the form of home improvement, roads and drainage but it is an assistance from PNPM not from KOTAKU and the government only chooses milih residents for i kut in socialization therefore we as other pinokalan community do not know and only know from others that socialization has been implemented about KOTAKU in Pinokalan Village. In the PROGRAM KOTAKU Pinokalan village is used as a companion village when compared to other villages that get assistance from KOTAKU Pinokalan Village can be said to be more eligible to get assistance from this KOTAKU program